Salt to the sea [compact disc, unabridged] : a novel - Sepetys, Ruta (Listening Library/Penguin Random House : Books on Tape, 2016)
"As World War II draws to a close, refugees try to escape the war's final dangers, only to find themselves aboard a ship with a target on its hull"--